The interrelationship between spatial organization, social interaction and landscape setting of The homestay towards Islamic built environment - Othman, Rashidi; Noor Azmee, Nur Amirah Azriati; Hashim, Khairusy Syakirin Has-Yun; Mahamod, Lukman Hakim; Ahmad Fadzillah, Nurrulhidayah (Human Resource Management Academic Research Society, 2019)
With the emergence of homestay programmed, Malaysia as a multi-racial country offers a golden opportunity for tourist to experience different cultures from different races. However, the homestay programmed offered does not implement the Shariah Compliant and introduce to the outsiders about the Islamic way of life as a Muslim country. Most of the homestay offer the guest to stay with the host’s family members without determining the space limitation within the house between the guest and host. Therefore, this research explores the complication exist in Muslim homestay. The issue about the spatial organization, space limitation, social interaction (ikhtilat) and landscape setting of the homestay will be identified and solved by implementing Shariah compliant. The selected homestay can be categorized as moderate in practicing the Shariah-compliant. In conclusion, the homestay providers are encouraged to apply and practice a Muslim-friendly and Shariah Compliant homestay system towards guests.